2017
DOI: 10.1080/14767058.2017.1319354
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid and acylcarnitine profiles in perinatal asphyxia: a case-control study

Abstract: We report UPLC-MS detectable alterations of amino acids and acylcarnitines in asphyxiated newborns at birth, that can serve as early diagnostic bedside biomarkers for HIE and predictors for its short-term outcome, and in the near future, as therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Among these amino acids according to various studies, alanine, creatinine, isoleucine, leucine, methionine, phenylalaline, taurine, and valine are the most significant (cf. Table 2) (29,31,(54)(55)(56). The same finding has been observed in several animal studies (25,27,28,33).…”
Section: Blood Levelssupporting
confidence: 86%
See 1 more Smart Citation
“…Among these amino acids according to various studies, alanine, creatinine, isoleucine, leucine, methionine, phenylalaline, taurine, and valine are the most significant (cf. Table 2) (29,31,(54)(55)(56). The same finding has been observed in several animal studies (25,27,28,33).…”
Section: Blood Levelssupporting
confidence: 86%
“…Of note, only methionine levels showed the same trend systematically across the different studies and only alanine was found to be significantly higher in patients with severe HIE (grade 3) in comparison to asphyxiated patients without HIE and the control groups (29). Some amino acid levels were also significantly different amongst asphyxiated neonates who went on to develop HIE vs. those who did not (29,56). The levels of alanine, phenylalanine, valine and leucine were significantly higher in the HIE group studied by El-Farghali et al (56).…”
Section: Blood Levelsmentioning
confidence: 68%
“…Disruptions in oxidative metabolism and the switch to anaerobic metabolism associated with HIE lead to mitochondrial membrane depolarization, intracellular accumulation of Ca 2+ and extracellular build-up of excitatory amino acids 1621 . The resulting metabolic acidosis is measurable, and others have reported alterations in amino acid and acyl-carnitine profiles similar to those described here 16,17,2226 . Our finding that tyrosine was the screening analyte most strongly associated with HIE in our cohort has also been previously observed 25 .…”
Section: Discussionsupporting
confidence: 82%
“…Lactate Plasma, urine, cord blood, CSF, brain tissue, ocular tissues [25,26,29,30,32,33,35,[38][39][40][41][42][45][46][47]49,51] Succinate Plasma, urine, cord blood, brain tissue [29,30,37,38,[40][41][42][43]45,47,49,50] Alanine Plasma, urine, cord blood, CSF, brain tissue [25,26,29,30,[37][38][39][40]48,49,52] Urine [36,38,45] BCAA, Branched Chain Amino Acids.…”
Section: Metabolite Sample Referencementioning
confidence: 99%
“…El-Farghali et al quantified the amino acids and acylcarnitines in cord blood dried spots collected from 45 full-term newborns exposed to PA (16 HIE and 29 non-HIE) and 20 matched healthy controls using UPLC-MS [52]. They detected differences in asphyctic samples with respect to controls but could also distinguish asphyxia from HIE.…”
Section: Human Studiesmentioning
confidence: 99%